Strategi Pengelolaan Usaha Dalam Upaya Keberlanjutan Badan Usaha Milik Desa (BUMDes) Studi Kasus: Desa Ombulodata Kec Kwandang Kab Gorontalo Utara - Rudin, Maryam Rudin; Isa, Rusli; Aneta, Asna (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the management strategy of Village-Owned Enterprises (Badan Usaha Milik Desa (BUMDes)) in an effort to sustain business in Ombulodata Village, Kwandang District, North Gorontalo Regency. The focus of the study includes organizational strategies, programs, resources, and institutions, as well as supporting and inhibiting factors in Badan Usaha Milik Desa (BUMDes) management. The research method uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. Research informants involve Badan Usaha Milik Desa (BUMDes) managers, village governments, and the community. The results of the study indicate that Ombulodata Badan Usaha Milik Desa (BUMDes) faces major challenges such as limited human resource quality, minimal community participation, bad debts, and dependence on the village budget. The management strategies implemented include local potential-based program planning, increasing human resource capacity through training, and optimizing natural resources such as agriculture and MSMEs. The main supporting factor is the commitment of the village government in allocating funds and regulations, while inhibiting factors include limited capital, lack of private sector support, and suboptimal internal coordination. The conclusion of the study emphasizes the importance of strengthening institutions, transparency of management, and synergy with external parties to ensure the sustainability of Badan Usaha Milik Desa (BUMDes). The implications of this research can be a reference for village governments in formulating more inclusive and sustainable Badan Usaha Milik Desa (BUMDes) development policies.